ANTECEDENTS OF EMPLOYEES JOB SATISFACTION AT PT SAMUDERA PERDANA - Fitria Elvira Hanafi; Justine Tanuwijaya; Dzihniyyah Fitria Nurhalizah; Zakiah Indah Safitri; Norzanah Mat Nor (Universitas Nusa Cendana, 2026)
This study aims to analyze the effects of psychological well-being, transformational leadership, employee engagement, and organizational culture on job satisfaction among employees of PT Samudera Perdana. The research was conducted using quantitative methods. Data was collected from 200 employees at PT Samudera Perdana. This research employs the partial least squares method with SmartPLS software. The results of hypothesis testing indicate that there is no positive effect of psychological well-being on job satisfaction and organizational culture on job satisfaction. However, there is a positive effect of transformational leadership on job satisfaction and employee engagement on job satisfaction. The findings of this study are expected to be utilized by companies to address existing issues and enhance the job satisfaction of employees at PT Samudera Perdana. Keywords: Psychological Well-being; Transformational Leadership; Job Satisfaction; Employee Engagement; Organizational Culture